Repurposing fed‐batch media and feeds for highly productive CHO perfusion processes. (8th May 2019) - Kuiper, Marcel; Spencer, Chris; Fäldt, Eric; Vuillemez, Audrey; Holmes, William; Samuelsson, Teres; Gruber, David; Castan, Andreas
Abstract: Perfusion is a cell culture mode that is gaining popularity for the manufacture of monoclonal antibodies and their derivatives. The cell culture media supporting perfusion culture need to support higher cell densities than those used in fed‐batch culture. Therefore, when switching from a fed‐batch to a perfusion mode, a new medium need to be developed which supports high cell densities, high productivity, and favorable product quality. We have developed a method for deriving perfusion culture media based on existing fed‐batch media and feeds. We show that we can obtain culture media that successfully support perfusion cultures in a single‐use rocking bioreactor system at cell‐specific perfusion rates below 25 pL −1 cell −1 day −1 . High productivities and favorable product quality are also achievable.